Co-inheritance of Southeast Asian ovalocytosis and Hb E: does it affect the red blood cells indices? - Riahi, Shahrzard; Lai, Mei I.; George, Elizabeth; Isahak, Ida Marhainis; Idris, Faridah; Md Noor, Sabariah (Advanced Medical and Dental Institute (AMDI), 2017)
Complete blood count (CBC) is used broadly to screen individual's general health status. Some inherited red blood cell (RBC) disorders influence the RBC parameters. Mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) are amongst the important RBC parameters used in thalassaemia-haemoglobinopathy screening [1-2]. Globin chain disorders and Southeast Asian Ovalocytosis (SAO) are common RBC disorders in Southeast Asian countries [3]. We evaluated the RBC parameters in patients with Hb E and those with SAO co-inheritance.